Influência da assimetria hemisférica na evolução funcional e perceptivo-visual após acidente vascular cerebral - Andrade, Suellen Mary Marinho dos Santos (2012)
This study aimed to analyze the evolution of functional and visual perception of patients with lesions in right and left hemisphere during the acute stage, subacute and chronic stroke. The study included 40 participants, involving patients with right-hemisphere lesions with and without hemineglect (RH+ and RH-, respectively), patients with lesions in the left hemisphere without hemineglect (LH-) and healthy subjects (CG). The socio-demographic and the clinic assessments were performed in hospital stay, and thereafter assessments were performed to functional evolution and visual perception. The analysis of the functional evolution involved spatial attention, postural control, gait and functional independence. As for the evolution of visual perception, we analyzed the contrast sensitivity curve of the participants through the psychophysical forced-choice, having been employed stimuli like sinusoidal grid with spatial frequencies of 0.6, 2.5 and 10.0 cycles per degree of visual angle (cpd). These assessments were performed after 1 month of vascular injury and repeated in 3 and 6 months after the episode of stroke. There were no significant differences between groups with respect to socio-demographic variables (χ2=6.42, p<0.08) and were not found direct correlations between neuropsychological performance and the side affected by stroke (p>0.05). Concerning the rate of recovery, there was improvement of all variables over the three stages of stroke. The patients (RH-, RH+ and LH-) lower performance achieved in the functional and visual perception when compared to healthy subjects. The group with damage to the left had a worse performance on tests of gait and functional independence, whereas the group with lesions to the right (RH- and RH+, respectively) showed greater impairment in spatial attention and postural control. Although both RH- and RH+ showed the same pattern of involvement, when compared the group of patients with lesions to the right, those with hemineglect had worse performance than those without hemineglect, in relation to the functional evolution. With regard to visual perception, the results showed that patients LH- were selectively more impaired in the detection of high frequencies, while patients with lesions to the right (RH- or RH+) had a worse performance in the detection of low frequencies. In relation to medium frequency, patients had a similar pattern of performance and presenting lower thresholds only for the CG. The findings obtained suggest that distinct processes related to visual and functional aspects, with both hemispheres participating in these processes in different ways.